Korelacioni mes rashësisë së endometriumit dhe qasjes patohistolog jike te pacientet në postemnopauzë - Tofiloska, Valentina; Asani, Pajtim (SHMSHM / AAMD, 2017)
Aim of the study was to trial to investigate the validity of the detected ultrasonic thickness of the endometrium in the prediction of endometrial cancer in postmenopausal patients with and without uterine bleeding, confirmed by histopathological analysis of material obtained by exploratory curettage of the endometrium. Material and Methods: This study included 120 patients recruited in post-menopausal age of the University Clinic of Gynecology and Obstetrics - Skopje, who were divided into two groups. Test group included 80 patients with postmenopausal detected ultrasonic endometrial thickness greater than or equal to 5mm. They were divided into two subgroups - subgroup A: Patients with uterine bleeding (40 patients) and subgroup B: patients without uterine bleeding (40 patients), which were divided based on ultrasound endometrial thickness of endometrium of 5-8mm; from 8-11mm; more than 11mm. The control group included 40 postmenopausal patients hospitalised because urogynecological pathology with previous ultrasound detected endometrial thickness of less than 5mm and orderly histopathological findings derived from material in exploratory curettage of endometrium. In each patient detailed history was taken and curettage exploratory fractionated and material was send to histopathological analysis. Results. The thickness of the endometrium is endometrial significant predictor of malignancy (p <0,05). With each millimeter increase in endometrium significantly increases the likelihood of endometrial malignancy of 1,178 [p = 0,002, 95% CI = 1,065-1,304] times. Conclusion: In postmenopausal patients likelihood of endometrial cancer significantly increases by 1,178 times.
Correlation between the thickness of the endometrium and the histopathological finding in postmenopausal patients
Keywords: postmenopausal women; endometrial thickness; endometrial malignancy